Analysis of the properties of a steering shaft used as a back-up for a steer-by-wire system during system failure - Baharom, Masri B; Hussain, Khalid; Day , A J (Professional Engineering Publishing, 2009)
An analysis is presented to determine the best selection criteria for the properties of a steering shaft to be used as a back-up apparatus for a steer-by-wire (SBW) system during system failure. The properties of interest are the steering-shaft stiffness and its damping coefficient. A mathematical model representing the failed state of an SBW system is derived, and a set of experiments to validate the model is presented. Once the model had been validated, further predictions of the car's handling behaviour for a range of steering-shaft properties and different road speeds were completed by simulations in MATLAB/Simulink. A minimum stiffness which did not cause the car to become unstable owing to overshoot was determined, and the minimum acceptable damping coefficient value was derived. It is concluded that the suggested stiffness and damping coefficient values increased the steering ratio, and the results of further investigations are presented, which confirm that the vehicle is safe to be driven in the event of SBW system failure if the recommended shaft properties are used.